A study of dynamic behaviour of proton exchange membrane fuel cell stack - Abdullah, Roslina; Saidi, Hamdani (2004)
The proton exchange membrane fuel cell (PEMFC) static has shown promise as the leading candidate for use as a non-polluting power source. It discharges water as waste, operates at low temperatures for quick start-up, and uses a solid polymer as an electrolyte which reduces both construction and safety complications. In order to study the dynamic behaviour of PEMFC stack, dynamic model is developed using MATLAB, a high performance technical computing software. The model is based on physical laws having clear significant in replicating the fuel cell system and can easily be used to set up different operational strategies. It consists of several submodels which are integrated to each other. The performances of the fuel cell stack such as thermodynamic efficiency, pressure and humidity profile are also described. As a whole, the output from the modeling technique can be varied to meet the needs of individual investigations as well as for the distribution results.